Molecular evolution of the def6/swap70 gene family and functional analysis of swap70a in zebrafish embryogenesis - Shuen, Wai Ho (2010)
Rho GTPases including Rac1, RhoA, and Cdc42 are molecular switches as for signal transduction. Cycling between the GTP-bound active state and GDPbound inactive state is tightly controlled by regulatory proteins. The exchange of GDP for GTP is catalysed by guanine nucleotide exchange factors (GEFs). Upon the activation of Rho GTPases through GEFs, downstream effector molecules are activated and thus trigger cellular responses such as actin cytoskeletal reorganisation, membrane ruffling, cell migration, and gene expression. Based on homology, there are three main families of Rho GEFs, Dbl family, Dock family, and def6/swap70 family. The large Dbl family is characterised through an invariable domain arrangement of an N-terminal catalytic dbl homology (DH) and a C-terminal regulatory pleckstrin homology (PH) domain whereas Dock family members lack the DH domain but instead contain a Dock homology region 2 (DHR2) domain. The def6/swap70 GEFs on the other hand contain an atypical and unique PH-DH like domain arrangement. Mammalian DEF6 and SWAP70 that exhibit a high similarity in their N-terminal ends containing a putative Ca2+ - binding EF hand are crucial mediators of signal transduction in T and B cells, respectively. Phylogenetic sequence analysis revealed that the atypical domain structure as well as the primary amino acid sequences of def6 and swap70 family members has been highly conserved in vertebrates and invertebrates. Whereas invertebrates have only one def6/swap70 gene, two genes have been identified in tetrapod species, and four to five genes have been identified in teleosts species. In zebrafish, five paralogous genes were identified: def6a, def6b, swap70a, swap70b and def6-like. Remarkably, the predicted secondary and tertiary structure of all def6/swap70 family members including the five proteins identified in zebrafish are very similar; most of them folding into a ‘donut-shape’ structure. The expression profile of the def6/swap70 genes during zebrafish development indicated that def6a and swap70a are expressed maternally as well as zygotically during early development whereas expression of the other three genes was restricted to later stages. Morpholino-mediated knockdown of swap70a using two different splice morpholinos resulted in a delay of zebrafish development likely to be due to impaired convergence and extension cell movements during gastrulation. In addition, development of brain, eyes, ears number of otoliths and tail formation was affected. Preliminary data using the AUG morpholino to target maternal and zygotic expression of swap70a indicate a more severe phenotype and high mortality of the morphants. Co-injection of GFP-tagged swap70a mRNA in low dose resulted in a partial rescue of the splice morpholinomediated phenotype. Over-expression of GFP-swap70a in high dose however, resulted also in developmental defects in eyes, number of otoliths and tail formation. The observed phenotype of swap70a morphants described here is reminiscent of the phenotype of def6a morphants that was shown to be downstream of Wnt5b in the non-canonical Wnt/PCP signalling pathway (Goudevenou et al. in preparation) regulating convergence extension cell movement during gastrulation. It is therefore tempting to speculate that swap70a has a similar role acting either in conjunction with or in parallel to def6a in the non-canonical Wnt signalling pathway.